Implementación de un parqueo inteligente mediante consolas expedidoras y validadores de tarjeta para el Bloque B de la UTC extensión La Maná. - Hidalgo Tovar, Kevin Rodrigo (2023)
The main objective of the research carried out was to implement smart parking through issuing consoles and card validators for block B of the UTC La Maná extension. To fulfill it, a qualitative methodology was established, under the types of bibliographic, field, and experimental research. The applied design was based on the experimental type. Among the relevant map conclusions the following were obtained; The implementation of smart parking was developed, managing to carry out the respective evaluations of smart parking performance through issuing consoles and card validators. To this end, four phases were proposed that allowed the respective evaluation, being the start phase where the system was started, followed by the start phase activating each of the respective protocols to access the smart parking system through validating cards. ; Likewise, the validation phase where the respective verification was carried out in the implementation of smart parking, verifying the operation of each component, including the photocells. Finally, the reader verification phase where their proper functioning was observed using the validator cards.